2001
DOI: 10.3102/00346543071003393
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Phonics Instruction Helps Students Learn to Read: Evidence from the National Reading Panel’s Meta-Analysis

Abstract: A quantitative meta-analysis evaluating the effects of systematic phonics instruction compared to unsystematic or no-phonics instruction on learning to read was conducted using 66 treatment-control comparisons derived from 38 experiments. The overall effect of phonics instruction on reading was moderate, d = 0.41. Effects persisted after instruction ended. Effects were larger when phonics instruction began early (d = 0.55) than after first grade (d = 0.27). Phonics benefited decoding, word reading, text compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
479
4
46

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 625 publications
(561 citation statements)
references
References 53 publications
32
479
4
46
Order By: Relevance
“…Systematic phonics involves teaching letter and sound links in a clear sequence. The overall effect size for systematic phonics compared to other approaches was estimated as +0.27, and the results largely confirmed a previous review by Ehri et al (2001). However, a combination of relatively few trials, and poor evidence or poorly-reported methods in some existing trials meant that the result cannot be seen as definitive, especially in relation to exactly how phonics should be taught.…”
Section: A Summary Of Evidence On the Effectiveness Of The General Phsupporting
confidence: 73%
“…Systematic phonics involves teaching letter and sound links in a clear sequence. The overall effect size for systematic phonics compared to other approaches was estimated as +0.27, and the results largely confirmed a previous review by Ehri et al (2001). However, a combination of relatively few trials, and poor evidence or poorly-reported methods in some existing trials meant that the result cannot be seen as definitive, especially in relation to exactly how phonics should be taught.…”
Section: A Summary Of Evidence On the Effectiveness Of The General Phsupporting
confidence: 73%
“…The first approach, which is often referred to as phonics/skills or code-based argues that, in first place, students should focus on individual letter-sound relationships, and that repetition and practice will enable them to recognise and write words accurately and correctly (Ehri et al 2001). This approach emphasises bottom-up processing with little recourse to higher level knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Code-based activities include teaching children how to name and write letters, rhyme words, relate letters to the sounds they make and sound out words (Torgesen et al 1994;Foorman et al 1998;Torgesen et al 1999;Rayner et al 2001). These practices are often associated with synthetic methods of literacy teaching (Ehri et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…À cet égard, un bilan des recherches réalisées au cours des dernières décennies (Ecalle et Magnan, 2002;Pressley, 1998) confirme l'importance d'une approche équilibrée intégrant le meilleur des méthodes globale et phonique 1 . La méthode globale propose des activités telles la lecture d'histoires et des jeux de lecture fonctionnelle, alors que la méthode phonique inclut des activités explicites et systématiques (Ehri, Nunes, Stahl et Willows, 2001) selon le nom et le son des lettres, des correspondances graphèmes-phonèmes et des habiletés métaphonologiques. Ces interventions phoniques, qui visent à apprendre le code alphabétique, constituent un apport crucial pour les élèves, notamment ceux qui sont à risque d'éprouver des difficultés d'apprentissage en lecture (Adams et Bruck,1995;Ehri, Nunes, Stahl et Willows, 2001;Pressley, 1998;Rayner, Foorman, Perfetti, Pesetsky et Seidenberg, 2001;Snow, Burns et Griffin, 1998).…”
Section: Introductionunclassified
“…La méthode globale propose des activités telles la lecture d'histoires et des jeux de lecture fonctionnelle, alors que la méthode phonique inclut des activités explicites et systématiques (Ehri, Nunes, Stahl et Willows, 2001) selon le nom et le son des lettres, des correspondances graphèmes-phonèmes et des habiletés métaphonologiques. Ces interventions phoniques, qui visent à apprendre le code alphabétique, constituent un apport crucial pour les élèves, notamment ceux qui sont à risque d'éprouver des difficultés d'apprentissage en lecture (Adams et Bruck,1995;Ehri, Nunes, Stahl et Willows, 2001;Pressley, 1998;Rayner, Foorman, Perfetti, Pesetsky et Seidenberg, 2001;Snow, Burns et Griffin, 1998). Cette connaissance du code alphabétique, si elle n'est pas suffisante pour assurer l'apprentissage de la lecture, en constitue néanmoins une condition essentielle (Alegria et Morais, 1991 ;Bus et van Ijzendoorn, 1999).…”
Section: Introductionunclassified